PENGARUH PERINGATAN BAHAYA MEROKOK PADA KEMASAN ROKOK TERHADAP PERILAKU PEROKOK - Miftahussurur, Miftahussurur; Darmawan, Arif; Soenarjanto, Bagus (Universitas 17 Agustus 1945 Surabaya, 2018)
This study was aimed to determine the effect of hazard warning on cigarette packs for disease asimpact on smoking among students at University of August 17, 1945 in Surabaya. Data collection wasdoing by spread questionnaires as many as 78 people respondents. Data analysis technique used wastechnique of correlation by Pearson’s product moment. The results showed that the correlation of theresults coefficient by - 0.296. This suggests that the negative relationship between warning the dangers ofsmoking to smokers behavior on August 17, 1945 students at the University of Surabaya. This negativerelationship means relations of